Machiavelli and us - Althusser, Louis (Verso, 1999)
"We do not publish our own drafts, that is, our own mistakes, but we do sometimes publish other people's," Louis Althusser once observed of Marx's early writings. Among his own posthumously released drafts, one, at least, is incontestably neither mistake nor out-take: the text of his lecture course on Machiavelli, originally delivered at the ecole Normale Superieure in 1972, intermittently revised up to the mid-1980s, and carefully prepared for publication after his death in 1990. Though only appearing as an occasional reference in the Marxist philosopher's oeuvre, Machiavelli was an unseen constant presence. For together with Spinoza and Marx, Machiavelli was a veritable Althusserian passion. Machiavelli and Us reveals why, and will be welcomed for the light it sheds on the richly complex thought of its author.